3.DETECTION OF NEW DELHI METALLO-BETA-LACTAMASE-1 (BLANDM-1) IN CARBAPENEM-RESISTANT PSEUDOMONAS AERUGINOSA ISOLATED FROM CLINICAL SAMPLES IN WASIT HOSPITALS (Iraqi Journal of Medical Sciences, 2019)
Background:Pseudomonas aeruginosa (P. aeruginosa) infections are clinical problem, it is a difficult to treat because of high resistant to many antibiotics (Multi-drug resistant) and a high risk of emergence of resistance during therapy. Carbapenems are therapeutic choice against infections caused by Gram-negative bacilli including strains of P. aeruginosa. New Delhi metallo-?-lactamase-1 (blaNDM-1) gene, an acquired class B carbapenemase. Dissemination predominantly involves transfer of the blaNDM-1 gene among promiscuous plasmids and clonal outbreaks. Bacteria with NDM-1 are typically resistant to nearly all antibiotics.Objective:To detect blaNDM-1 in the isolates of P. aeruginosa, which were recovered from various clinical samples from hospitalized patients in Wasit hospitals.Methods: This cross-sectional study involved 200 clinical samples were collected from three major hospitals in Wasit province. Samples were inoculated in Mackonkey and blood agar for primary isolation and then biochemical tests were used to confirm diagnosis of P. aeruginosa. The susceptibility test for 14 types of antibacterial drugs were tested by using disk diffusion method. Chromosomal and plasmid DNA were extracted by using special methods.Results: Out of 36 carbapenems resistant P. aeruginosa (CRPA) isolates, there were 18 isolates (50%) positive for blaNDM-1 gene.Conclusion: Rate of occurrence of blaNDM-1producers is highest among carbapenem-resistant P. aeruginosa isolated from clinical samples in Wasit hospitals. Therefore, its recognizable proof in clinical bacterial diseases will be suspected in any carbapenem resistance P. aeruginosa.Keywords: P. aeruginosa; carbapenems; metallo-?-lactamase; blaNDM-1Citation: Hussein ZK, Kadhim HS, Hassan JS. Detection of New Delhi metallo-beta-lactamase-1 (blaNDM-1) in carbapenem-resistant pseudomonas aeruginosa isolated from clinical samples in Wasit hospitals. Iraqi JMS. 2018; 16(3): 239-246. doi: 10.22578/IJMS.16.3.3
Keywords: P aeruginosa carbapenems metallolactamase blaNDM1